Analysis of dependence of grade point average over psychological factors incorporating advanced data mining. (27th October 2022) - Khanna, Leena; Singh, Shailendra Narayan; Kumar, Rita; Alam, Mansaf
Academic performance of any individual is dependent upon numerous aspects regarding the day to day life of the individual under consideration. Academic performance is measured in terms of the grade point average or GPA as it is called. Grade point average is dependent not only on the faculty but also on various cognitive and non-cognitive factors. The non-cognitive or the psychological parameters include factors like study habits, social anxiety, extraversion and allied concepts. In this study, a detail analysis of numerous psychological factors that can impact the grade point is studied. Bases on the various psychological factors studied, the performance of an individual is classified and in forthcoming examination can be forecasted.